Scoping Review: Comparison Of Organizational Culture Engineering Concepts Of Habit Formation, Shook, And Schein Models In Project Organizations - Iftitah Ruwana; Nanta Sigit; Nelly Budiharti; Prima Vitasari; Renny Septiari; Mariza Kertaningtyas; Diah Wilis Basuki; Sutanto Hidayat (International Journal of Technology and Education Research, 2025)
Organizational culture is part of an integrated system, whether it's a structured organization or an unstructured community. Most research on organizational culture discusses the relationship between culture and other variables within the organization, or how to measure culture within an organization. In an era of technological advancement, rapid change, and high complexity, a method is needed to effectively change organizational culture. This study attempts to examine three concepts that offer methods for changing organizational culture. All three concepts offer the same paradigm: that cultural change does not begin with changing something abstract and soft-system. Rather, cultural change needs to begin with changing something concrete and tangible. This includes procedures, work methods, infrastructure, and other artifacts within the company organization. These three concepts are then synthesized to produce a proposed concept. This proposed concept is expected to be easier to implement and understand for activists and researchers in the field of organizational culture.